Evaluation of drought-tolerant endophytic fungus Talaromyces purpureogenus as a bioinoculant for wheat seedlings under normal and drought-stressed circumstances - Kaur, Ramandeep; Saxena, Sanjai (Folia microbiologica, 2023)
The present work is aimed to hypothesize that fungal endophytes associated with wheat (Triticum aestivum L.) plants can play a variety of roles in biotechnology including plant growth. Out of 67 fungal isolates, five maximum drought-tolerant isolates were used to check their various plant growth-promoting traits, antioxidants, and antifungal activities under secondary screening. Fungal isolate #8TAKS-3a exhibited the maximum drought tolerance capacity and potential to produce auxin, gibberellic acid, ACC deaminase, phosphate, zinc solubilization, ammonia, siderophore, and extracellular enzyme activities followed by #6TAKR-1a isolate. In terms of antioxidant activities, #8TAKS-3a culture also showed maximum DPPH scavenging, total antioxidant, and NO-scavenging activities. However, #6TAKR-1a exhibited maximum total flavonoid content, total phenolic content, and Fe-reducing power and also the highest growth inhibition of Aspergillus niger (ITCC 6152) and Colletotrichum sp. (ITCC 6152). Based on morphological characters and multi-locus phylogenetic analysis of the nuc rDNA internal transcribed spacer region (ITS1-5.8S-ITS2 = ITS), β-tubulin (TUB 2), and RNA polymerase II second largest subunit (RPB2) genes, potent fungal isolate #8TAKS-3a was identified as Talaromyces purpureogenus. Under the in vitro conditions, T. purpureogenus (#8TAKS-3a) was used as a bioinoculant that displayed a significant increase in various physio-biochemical growth parameters under normal and stressed conditions (p < 0.05). Our results indicate that drought stress-tolerant T. purpureogenus can be further used for field testing as a growth promoter.
Keywords: Wheat; Bioinoculant; Endophytes; antioxidancia; Triticum; období sucha; Droughts; pšenice; Endophytic fungi; Phylogeny; Antioxidants; Seedlings; fylogeneze; endofyty; semenáček; Plant-growth promoter; Drought; Talaromyces